2017
DOI: 10.5152/eurasianjmed.2017.17126
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Infliximab Injection to Treat Experimental Endophthalmitis

Abstract: Objective: The purpose of this study was to compare the use of an intravitreal injection of infliximab and of dexamethasone combined with vancomycin to treat experimental endophthalmitis induced by Staphylococcus epidermidis. Materials and Methods: The study was conducted between March 25 and April 13, 2012. Twenty-five six-monthold healthy rabbits were used, each weighing 2.5-3 kg. The rabbits were randomized into five groups with five animals per group. Endophthalmitis was induced by 0.1 mL (103 colony-formi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…156,157 A study on experimental endophthalmitis using S. epidermidis showed that infliximab was as effective as dexamethasone in controlling inflammation when injected intravitreally along with vancomycin. 158 In contrast to this, two studies which compared intravenous and intravitreal infliximab showed significantly better control of inflammation with the intravenous regimen. One of these studies showed no change with intravitreal dose 159 while the other showed exacerbation of inflammation with intravitreal injection.…”
Section: Infliximabmentioning
confidence: 92%
“…156,157 A study on experimental endophthalmitis using S. epidermidis showed that infliximab was as effective as dexamethasone in controlling inflammation when injected intravitreally along with vancomycin. 158 In contrast to this, two studies which compared intravenous and intravitreal infliximab showed significantly better control of inflammation with the intravenous regimen. One of these studies showed no change with intravitreal dose 159 while the other showed exacerbation of inflammation with intravitreal injection.…”
Section: Infliximabmentioning
confidence: 92%